Optimizing hybrid insulation systems for diverse climates: A comparative analysis of composite material combinations in residential buildings - Khoso, Salim; Bakhtavar, Ezzeddin; Abouyoussef, Ahmed; Zahid, Muhammad; Hewage, Kasun; Sadiq, Rehan (Energy and buildings, 2025)
With increasing concerns over global warming and climate change, achieving environmental sustainability in residential construction has become a priority. Traditional insulation materials often struggle to maintain optimal thermal and energy efficiency across varying climatic conditions, highlighting the need for innovative hybrid systems. This study systematically evaluates hybrid insulation systems through simulation-based analysis and a multi-objective mathematical model to optimize energy performance in residential buildings. Simulations were conducted to analyze different material configurations in two distinct Canadian climates: the mild conditions of Vancouver and the cold environment of Winnipeg. The assessment considered thermal resistance, energy consumption, and operational emissions. A multi-objective binary integer programming model was developed to prioritize material combinations based on five key criteria: accessibility to materials, total energy consumption, operational cost, operational environmental impacts, and societal aesthetics. The model incorporated priority weights to align with diverse stakeholder preferences, enabling decision-makers to tailor the optimization process based on specific goals. The results demonstrate that Combination 4, comprising limestone, oriented strand board (OSB), and clay tiles, consistently outperformed other configurations in both climates. In Vancouver, this combination reduced energy consumption by 47.7% compared to a conventional 6-inch concrete wall, while in Winnipeg, it achieved a 49.8% reduction. Furthermore, Combination 4 exhibited the lowest operational emissions and costs, making it the most cost-effective and sustainable choice. These findings provide valuable insights for architects, policymakers, and construction professionals seeking resilient, energy-efficient, and environmentally sustainable insulation solutions adaptable to diverse climatic conditions.